Proposed Business Strategies of Social Enterprise: Teman Tanpabatas (The Indonesian Journal of Business Administration, 2021)
Teman Tanpabatas is a social enterprise that has a mission to empower person with disability, so people with disability can independently economy after graduated from Special School. Understanding PWD might be complex yet challenging. Nowadays more then 21.84 million people with disability live in Indonesia. There are also more than 74.4% people with disability still do not have a work in their life. All the stakeholders must give their best support to solve this problem. SLB graduates who still do not have a place for life after they graduate from school and in society. It should be prepared when they are still at school. Teman Tanpabatas was established as the part of community and become the bridge between PWD and the other stakeholders, so that awareness about the economic development in PWD will be increased. For this reason, it is very important to develop skills for PWD and non-PWD so that it remains sustainable so that it can develop a value-selling product that involves PWD, SLB, and the community. After doing some research and strategic analysis, author propose Teman Tanpabats strategies to improve its performance. In the end, TTB could become a platform for business and product development for PWD.Keywords: Social enterprise, business strategy, performance, people with disabilities, Teman Tanpabatas